Structural basis for cooperativity of CRM1 export complex formation - Monecke, Thomas; Haselbach, David; Voß, Béla; Russek, Andreas; Neumann, Piotr; Thomson, Emma; Hurt, Ed; Zachariae, Ulrich; Stark, Holger; Grubmüller, Helmut; Dickmanns, Achim; Ficner, Ralf (Proceedings of the National Academy of Sciences of the United States of America, 2013)
In eukaryotes, the nucleocytoplasmic transport of macromolecules is mainly mediated by soluble nuclear transport receptors of the karyopherin-β superfamily termed importins and exportins. The highly versatile exportin chromosome region maintenance 1 (CRM1) is essential for nuclear depletion of numerous structurally and functionally unrelated protein and ribonucleoprotein cargoes. CRM1 has been shown to adopt a toroidal structure in several functional transport complexes and was thought to maintain this conformation throughout the entire nucleocytoplasmic transport cycle. We solved crystal structures of free CRM1 from the thermophilic eukaryote Chaetomium thermophilum. Surprisingly, unbound CRM1 exhibits an overall extended and pitched superhelical conformation. The two regulatory regions, namely the acidic loop and the C-terminal α-helix, are dramatically repositioned in free CRM1 in comparison with the ternary CRM1-Ran-Snurportin1 export complex. Single-particle EM analysis demonstrates that, in a noncrystalline environment, free CRM1 exists in equilibrium between extended, superhelical and compact, ring-like conformations. Molecular dynamics simulations show that the C-terminal helix plays an important role in regulating the transition from an extended to a compact conformation and reveal how the binding site for nuclear export signals of cargoes is modulated by different CRM1 conformations. Combining these results, we propose a model for the cooperativity of CRM1 export complex assembly involving the long-range allosteric communication between the distant binding sites of GTP-bound Ran and cargo.